A minimally invasive flexible electrode array for simultaneous recording of ECoG signals from multiple brain regions. Issue 12 (6th May 2021) - Jeong, Ui-Jin; Lee, Jungpyo; Chou, Namsun; Kim, Kanghwan; Shin, Hyogeun; Chae, Uikyu; Yu, Hyun-Yong; Cho, Il-Joo
Abstract : The minimal invasiveness of electrocorticography (ECoG) enabled its widespread use in clinical areas as well as in neuroscience research. Abstract : The minimal invasiveness of electrocorticography (ECoG) enabled its widespread use in clinical areas as well as in neuroscience research. However, most existing ECoG arrays require that the entire surface area of the brain that is to be recorded be exposed through a large craniotomy. We propose a device that overcomes this limitation, i.e., a minimally invasive, polyimide-based flexible array of electrodes that can enable the recording of ECoG signals in multiple regions of the brain with minimal exposure of the surface of the brain. Magnetic force-assisted positioning of a flexible electrode array enables recording from distant brain regions with a small cranial window. Also, a biodegradable organic compound used for attaching a magnet on the electrodes allows simple retrieval of the magnet. We demonstrate with an in vivo chronic recording that an implanted ECoG electrode array can record ECoG signals from the visual cortex and the motor cortex during a rat's free behavior. Our results indicate that the proposed device induced minimal damage to the animal. We expect the proposed device to be utilized for experiments for large-scale brain circuit analyses as well as clinical applications for intra-operative monitoring of epileptic activity.